2022
DOI: 10.1039/d2fo01705a
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of allergenicity of roasted cod with Allium spp.: characterization of principal anti-allergenic constituent and action mechanism

Abstract: Cod is rich in high-quality proteins and is a popular ingredient in many cuisines. However, it has also been a culprit in many seafood allergy cases. In the present study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A study in Chongqing, a city in China, showed that the incidence of food allergies among infants and young children increased significantly from 3.5% in 1999 to 7.7% in 2009 [6]. Codfish is a popular ingredient in many delicacies by reason of containing rich high-quality proteins, but it is the culprit of many seafood allergies [7]. Shrimp, crab, beef, and fish are also common animal foods in southern China that cause a high allergic rate among children [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Chongqing, a city in China, showed that the incidence of food allergies among infants and young children increased significantly from 3.5% in 1999 to 7.7% in 2009 [6]. Codfish is a popular ingredient in many delicacies by reason of containing rich high-quality proteins, but it is the culprit of many seafood allergies [7]. Shrimp, crab, beef, and fish are also common animal foods in southern China that cause a high allergic rate among children [8][9][10].…”
Section: Introductionmentioning
confidence: 99%